生物计量信息监测系统 (2020)
提供了一种用于监测在床上的对象的生物计量信息的生物计量信息监测系统(100)。该系统包括：多个负载检测器(11、12、13、14)，其被放置在床(BD)上或者床的床脚下方并且检测对象的负载；重心位置计算单元(31)，其基于所检测到的对象的负载来获取对象的重心位置的时间变化；身体运动信息确定单元(37)，其基于所获取的对象的重心位置的时间变化来获取关于对象的身体运动的信息；以及呼吸频率计算单元(32)，其基于所获取的对象的重心位置的时间变化和由身体运动信息确定单元(37)获取的关于对象的身体运动的信息来计算对象的呼吸频率。 There is provided a biological information monitoring system for monitoring biological information of a subject on a bed, the system comprising: detectors which detect load of the subject; a center of gravity position calculating unit which acquires temporal variation of a center of gravity position of the subject based on the detected load; a body motion information determining unit which acquires information on body motion of the subject based on the acquired temporal variation; and a respiratory rate calculating unit which calculates a respiratory rate of the subject based on the acquired temporal variation and the information on the body motion of the subject. The body motion information includes information on large and small body motions of the